Analysis of Indonesian Freelancers' Strategies in Using The Upwork Platform - Daffa Malik Fadlurrahman; Putri Wulandari; Muhammad Arif Abdul Hakim; Andri Waskito (Yayasan Edukasi Cakrawala Nusantara, 2026)
This study aims to determine the strategies of Indonesian freelancers in facing competition, threats of fraud, and the use of Connect on the Upwork platform. This study is a qualitative study with a descriptive approach using data collection techniques through interviews, observation, and documentation. The data obtained were then analyzed using qualitative data analysis techniques through the stages of data reduction, data presentation, and conclusion drawing/verification. This study was conducted on Indonesian freelancers who are active on the Upwork platform and spread across various regions. Based on the results of the field research, the author concludes that Indonesian freelancers have developed specific strategies to deal with the challenges of global competition, the risk of fraud from clients, and the limitations of the Connect system. The strategies implemented include profile optimization, focusing on proposal content and digital portfolios for personal branding, leveraging online communities to disseminate information and raise awareness about fraud schemes, and managing Connect wisely to enhance project application efficiency. These methods serve as adaptive mechanisms to improve the effectiveness of online freelance work and promote the development of a safer and more competitive digital work environment.